Simple and Versatile Nitrooxylation: Noncyclic Hypervalent Iodine Nitrooxylating Reagent. (27th March 2023) - Cheng, Xuan; Yin, Quan; Jiang, Yu‐Xuan; Jiang, Ling‐Feng; Li, Si‐Yuan; Cheng, Yi‐Fei; Sun, Xin‐Chang; Peng, Lujun; Zhong, Cheng; Deng, Qing‐Hai
Abstract: Organic nitrates are broadly applied as pharmaceuticals (acting as efficient nitric oxide donor), energetic materials, building blocks in organic synthesis, etc. However, practical and direct methods to access organic nitrates efficiently are still rare, mainly due to the lack of powerful nitrooxylating reagents. Herein, we report bench‐stable and highly reactive noncyclic hypervalent iodine nitrooxylating reagents, oxybis(aryl‐λ 3 ‐iodanediyl) dinitrates (OAIDNs, 2 ), which are prepared just by using aryliodine diacetate and HNO3 . The reagents are used to achieve a mild and operationally simple protocol to access diverse organic nitrates. By employing of 2, zinc‐catalyzed regioselective nitrooxylation of cyclopropyl silyl ethers is realized efficiently to access the corresponding β‐nitrooxy ketones with high functional‐group tolerance. Moreover, a series of direct and catalyst‐free nitrooxylations of enolizable C−H bonds are carried out smoothly to afford the desired organic nitrates within minutes by just mixing the substrates with 2 in dichloromethane. Abstract : A bench‐stable and highly reactive noncyclic hypervalent iodine nitrooxylating reagent is prepared from aryliodine diacetate and HNO3 . This reagent facilitates the zinc‐catalyzed regioselective nitrooxylation of cyclopropyl silyl ethers with broad scope, and also can be used in the nitrooxylation of various enolizable C−H bonds.